VARIOUS TRAITS OF PB-2 BIRD IN INTENSIVE SYSTEM OF MANAGEMENT (Indian Journal of Animal Production and Management, 2014)
An experiment was conducted to study the different traits of PB-2 bird being maintained under AICRP on Poultry Breeding, Department of Poultry Science, College of Veterinary Science, Assam Agricultural University, Khanapara, Guwahati-22 under intensive system of rearing. The result in respect of body weight, conformation traits, feed conversion ratio, mortality and carcass traits were recorded during the study.
Keywords: PB-2 bird; Age at sexual maturity; Hatchability; Carcass traits